Antibody against progesterone in local rabbit following low dose of progesterone injection - Suyadi Suyadi; Sri Wahjuningsih; Aulani'am Aulani'am; Achadiah Rachmawati; P. Srianto; M. Pangestu (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2011)
ABSTRACT: Antibody against progesgerone was produced from serum of local rabbit following low dose of progesterone injection: While a control group (Control; n=5) was injected with Freund's adjuvant solution in aquadest, the treatment groups were either firstly injected with progesterone conjugated to Freund's Adjuvant (P--CFA, 150 p.l : 150 pl) or progesterone conjugated to Freund's Adjuvant and bovine serum albumin (P-CFA-BSA; 135 p;l : 150 tt1 : 15 gl). Twice boostering injections were adminstered using incomplete Freund's Adjuvant on day 14 and 52 after first immunization. Weekly bleeding for serum collection were done from 1 week following first booster immunization to week 10, Using ELISA technique it was shown that the antibody titer to progesterone after first and second booster immunization in the P-CFA groug was higher than Control- and P-CFA-BSA groups. The antibody titer in the P-CFA-BSA remained low similar in the Control group:Key words: antibody; progesterone; rabbit